PENGARUH MUTASI TERHADAP SEMANGAT KERJA PEGAWAI NEGERI SIPIL PADA KANTOR PELAYANAN PAJAK PRATAMA KOTA PEMATANG SIANTAR - Arnimisari Juliana Ambarita; Hatta Ridho (PERSPEKTIF, 2016)
The Organization must develop its own human resources so that the organization develop. Employee development efforts i.e. mutation with the process of the transfer of functions, responsibilities and status of employees. Boost morale of mutation with the new environment. Morale is an employee-owned enthusiast-level to complete its work. The purpose of this research is to know the mutation effect positive or negative towards the morale of civil servants at KPP Pratama Kota Pematang Siantar. The method used is quantitative. The data processed by the correlation coefficient and the determinant Moment Product to see the great influence of the variable X against Y variable. Based on the results of the research of the variable X and Y variables, then retrieved rxy= 0.404 showed a mutation effect on morale of civil servants of KPP Pratama Kota Pematang Siantar and the magnitud is 16,32%